Recurrence of a Langerhans Cell Histiocytosis bone lesion in a different site: A case report. (March 2022) - Al Abdulsalam, Ali; Kapila, Kusum; Alherz, Mohammad; Alsayegh, Mohammad
Abstract: Introduction: Langerhans' Cell Histiocytosis is a rare disease of unknown etiology, the pathogenesis of which involves both reactive and neoplastic processes. Despite potential resolution with conservative management, a rare recurrence in a distant site after 3 years from presentation in this case highlights the variability in the course of the disease and the need for larger studies to enable recognition and evidence-based management. Case presentation: We present an unusual case below of a 25-year-old gentleman who presented with sternal pain and tenderness. Imaging showed a lytic lesion in the sternum which resolved spontaneously with oral analgesia. He presented 3 years later with back pain and a similar lytic lesion in the iliac bone was found and diagnosed as recurrent Langerhans Cell Histiocytosis with a biopsy. Clinical discussion: There is a diverse array of documented presentations of Langerhans Cell Histiocytosis involving single or multiple systems, while its progression and outcomes are equally unpredictable from the current literature. In order to facilitate wider recognition, Langerhans Cell Histiocytosis should be considered in the differential diagnosis of recurrent lytic bone lesions. Conclusion: Although this is a rare disease, there is currently an unmet need for understanding the determinants of recurrence and response to treatment. Highlights: Langerhans Cell Histiocytosis is a rare disease of reactive and neoplastic pathologies. Spontaneous remissions can be followed by recurrences in distant sites. It should be considered in the differential diagnosis of recurring lytic bone lesions.